1996
DOI: 10.1007/bf00227888
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated expression of heme oxygenase-1 and ubiquitin in the porcine heart subjected to ischemia and reperfusion

Abstract: Heme oxygenase (HO) isozymes, HO-1 and HO-2 catalyze the cleavage of heme b to form the antioxidant biliverdin IXa, iron and the putative cellular messenger carbon monoxide (CO). Heat and stress have been reported to induce the expression of HO-1, in analogy to ubiquitin, a protein of 8 kDa involved in ATP dependent proteolysis. Earlier, we have shown in anesthetized pigs that brief periods of coronary artery occlusion followed by reperfusion produce prolonged regional cardiac dysfunction (stunning) associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 39 publications
2
29
0
1
Order By: Relevance
“…Heme oxygenase-1 plays a central role in myocardial protection from I/R injury. The enzyme is induced several fold by hypoxia and reoxygenation [28,29], and genetic mouse models of HO-1 deficiency have greater propensity towards ischemia and hyperoxia induced tissue injury [12,13]. Moreover, pre-emptive delivery of HO-1 gene markedly reduces infarct size following acute I/R [10,11], suggesting that enhanced basal level of HO-1 preconditions the myocardium [12,30] and renders it resistant to subsequent episodes of I/R injury [14].…”
Section: Discussionmentioning
confidence: 99%
“…Heme oxygenase-1 plays a central role in myocardial protection from I/R injury. The enzyme is induced several fold by hypoxia and reoxygenation [28,29], and genetic mouse models of HO-1 deficiency have greater propensity towards ischemia and hyperoxia induced tissue injury [12,13]. Moreover, pre-emptive delivery of HO-1 gene markedly reduces infarct size following acute I/R [10,11], suggesting that enhanced basal level of HO-1 preconditions the myocardium [12,30] and renders it resistant to subsequent episodes of I/R injury [14].…”
Section: Discussionmentioning
confidence: 99%
“…Under pathophysiological conditions, however, HO-1, but not HO-2, is induced in the heart and blood vessels (13)(14)(15)(16)(17). For example, we and others have reported that bacterial endotoxin markedly increases HO-1 expression in VSMCs and cardiomyocytes in vivo (15,17,18).…”
Section: Introductionmentioning
confidence: 87%
“…The frozen tissue was transferred to guanidium thiocyanate bu er, homogenized (Ultra-Turrax homogenizer, model T8, Janke & Kunkel GmbH, Staufen, Germany) and the total RNA was extracted as described earlier (Chomczynski & Sacchi, 1987;Sharma et al, 1996). The RNA concentration was measured by UV absorbance at 260 nm using a Gene Quant RNA/DNA calculator (Pharmacia-LKB, Biochrom, UK) and the quality of RNA was assessed by OD 260 /OD 280 ratio of 41.8 as well as by formaldehyde-agarose gel electrophoresis.…”
Section: Mrna Isolation and Cdna Synthesismentioning
confidence: 99%